Factor influence job performance of the Malaysian Immigration Officers / Nur Ayunis Syairah Mohamad Zaidi and Nurul Hidayana Mohd Noor - Mohamad Zaidi, Nur Ayunis Syairah; Mohd Noor, Nurul Hidayana (2021)
In this study, the meaning of job performance refers to as defined by Islami, Mulolli, and Mustafa (2018). They consider management success as a planned mechanism with core elements in consensus, evaluation, assistance, input, and constructive strengthening. In addition, Bataineh (2017) highlights job performance as a blend of the productivity and efficiency of everyday activities to fulfill stakeholders' needs. According to Isaac, Abdullah, Ramayah, and Mutahar (2017), workers believe that their Internet implementation helps them improve their mission and acquire training and communication efficiency, leading to enhanced individual and corporate results. While Pawirosumarto, Sarjana, and Gunawan (2017) have on the other side a tide between job output and work climate that includes both physical and nonphysical influences for workers that have a positive and vital impact on enhancing employee performance. However, Smith and Bitittc (2017) emphasize enhancing success assessment and performance improvement processes as variables that increase employee involvement. Mensah (2018) often endorse their proposals as a critical success driver for business considered talent management, who are at the heart of our very competitive and volatile business climate of the 21st century. Therefore, this study aimed to examine the factors influence of training, reward, and appraisal system on the job performance of Malaysian Immigration Officers.